Ethnic‐Racial Identity and Friendships in Early Adolescence. Issue 3 (21st March 2017) - Rivas‐Drake, Deborah; Umaña‐Taylor, Adriana J.; Schaefer, David R.; Medina, Michael
Abstract : The current study examined how adolescents' ethnic‐racial identity (ERI) informed the demographic diversity of their friendship network (Goal 1) and the extent of similarity between adolescents' and their friends' ERI (Goal 2). Participants were sixth and seventh grade students ( N = 353; M age = 11.88, SD = .73; 50% girls; 29% African American, 31% White, 13% Latino) in the Midwestern U.S. Results from longitudinal cross‐lagged models (Goal 1) indicated that having more diverse friendships at T2 was associated with greater T3 ERI exploration among all youth. In addition, boys who reported higher ERI resolution at T1 had more diverse friendships at T2. Furthermore, findings from longitudinal social network analyses (SNA; Goal 2) suggested that influence drove similarity between adolescents and their friends in ERI exploration and resolution. Abstract : The title for this Special Section isContext and Ethnic/Racial Identity, edited by Eleanor K. Seaton, Stephen Quintana, Maykel Verkuyten, and Gilbert C. Gee